Turkish pharmacists' counseling practices and attitudes regarding emergency contraceptive pills - RABUŞ, ŞULE (SPRINGER, 2012)
Objective The aim of this study is to assess Turkish pharmacists' counseling practices and attitudes regarding emergency contraception pills (ECPs). Setting This cross-sectional observational study was conducted via a web-based survey in Turkey. Methods Pharmacists registered at a professional web site (n = 822) were invited to fill in the study questionnaire; 624 questionnaires were completed and further analyzed. Pharmacists who agreed to participate in the study completed the questionnaire which was structured to elicit their demography, professional experience, counseling practices and attitudes regarding ECP. Attitudes were measured by 18 items under four domains: reproductive health; information and availability; risk behavior and regulatory restrictions. The answer choices consisted of five items as: totally agree, agree, neither agree nor disagree, disagree and totally disagree. Main outcome Measures The rate of counseling on various aspects of the ECPs and the rate of negative/positive attitudes. Results The aspects most frequently counseled on by the pharmacists were dosage, timeframes, efficacy and pregnancy testing. Less frequently counseled aspects were mechanism of action, methods of contraception and side-effects. In general, the pharmacists displayed positive attitudes towards all domains of the survey; while they were negative to the items suggesting that ECP should be sold only to women and only on prescription. Another interesting finding is that 58 % of the pharmacists agreed with the item suggesting limiting the ECP sales to those over 18 years of age. Conclusions Our results showed that the pharmacists served the clients in need of emergency contraception more frequently than the other health-care providers and in general had favorable attitudes towards ECP. Some aspects of their counseling practices need to be improved. This can be accomplished through continuous education programs that would equip them with the competence to provide counseling on emergency contraception which will in turn help prevent unintended pregnancies and reduce abortion rates.
Keywords: Attitude; Counseling; Emergency contraception pill; Non-prescription; Pharmacist; Turkey; OVER-THE-COUNTER; RANDOMIZED CONTROLLED-TRIAL; HEALTH-CARE PROVIDERS; YUZPE REGIMEN; KNOWLEDGE; PERCEPTIONS; TURKEY; ACCESS